1752 N.Y. Laws 199 - (:unkn) unknown (My University, 1730)
Ch. 560, § 20: Prohibited slaves from having or using any gun, pistol, sword, club, or any other kind of weapon. Violators punished by up to twenty lashes.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES